Paraphrase Practices in Academic Writing of Nursing Science Study Program, STIK Bina Husada Palembang - Agus Wahyudi; Arief Pamuji (International Journal of Integrative Sciences, 2023)
Paraphrasing has two main purposes, namely to avoid plagiarism and to make ideas easier to understand. The purpose of this research is to answer the following questions: 1. How are the paraphrasing results of the students of the Nursing Study Program STIK Bina Husada Palembang?, and 2. What are their perceptions of paraphrasing?. This research was conducted on May 27th, 2023, out of 38 students registered, only 34 students from the Nursing Science Study Program STIK Bina Husada Palembang participated in this research The students were asked to paraphrase a text containing 119 words entitled "Why is the millennial generation vulnerable to smartphone addiction?" the pparticipants were first shown the text and asked to read to gain understanding, then they were asked to paraphrase the paragraph. The results of this study indicated that the students of the Nursing Study Program at STIK Bina Husada Palembang are divided into 2 groups, namely: those who successfully paraphrase and those who fail, however, the limitations of the study should be noticed for further research. The results of this study have implications for teaching, bearing in mind that there are still students who avoid changing words and sentence structures when paraphrasing, this is due to limited vocabulary in making effective paraphrasing